Financial systems and economic growth : credit, crises, and regulation from the 19th century to the present - Rousseau, Peter L.; Wachtel, Paul, 1945- (Cambridge : Cambridge University Press, 2017)
Throughout much of the twentieth century, economists paid little heed to the role of financial intermediaries in procuring a beneficial allocation of capital. But by the end of the century some financial historians had begun to turn the tide, and the phrase 'finance-growth nexus' became part of the lexicon of modern economics. Recent experience has added another dimension in that countries with broader, deeper and more active financial systems might be prone to financial crises, particularly if regulatory structures are inadequate. In this book, Peter L. Rousseau and Paul Wachtel have gathered together some of today's most distinguished financial historians to examine this finance-growth nexus from historical and modern perspectives. Some essays examine the nexus in a particular historical or cross-country context. Others, in the light of recent experience, explore the expanded nexus of finance, growth, crises, and regulation.
Title from publisher's bibliographic system (viewed on 24 Oct 2017).
Keywords: elektronické knihy; electronic books; Economic development; Finance, Public; Monetary policy; Banks and banking